EVALUASI TINGKAT KESIAPSIAGAAN DAN RESPONS TIM KERJA DALAM OPERASI SAR PADA KANTOR PENCARIAN DAN PERTOLONGAN MANOKWARI - Habsyi, Faraj Reza; Resi, Yohanes Damaskus; Suharsono, Desi Suharnani (JURNAL LENTERA BISNIS, 2026)
This study aims to evaluate the level of preparedness and team response during search and rescue (SAR) operations at the Manokwari Search and Rescue Office. Delays in response time and varying levels of competence among team members prompted the need for an in-depth assessment of human resource readiness and operational systems in the field. A descriptive qualitative approach was employed to explore personnel preparedness, coordination effectiveness, and logistical support. Data were collected through direct observation, in-depth interviews, and document analysis involving eight informants comprising field personnel, support staff, and operational leaders. Data were analyzed using reduction, categorization, and thematic interpretation techniques based on the Miles and Huberman model. The findings reveal that personnel preparedness is at a relatively good level, supported by adequate understanding of standard operating procedures, although technical training remains inconsistent. Equipment and logistics are generally available, yet distribution to remote areas continues to hinder operational speed. Cross-sector communication and coordination remain suboptimal due to signal interference and lack of standardized collaboration mechanisms. The average response time of 35 minutes slightly exceeds the national standard; however, operational effectiveness remains high with an 83% success rate in rescue operations. Strengthening preparedness requires integrated training, equipment renewal, and modernization of communication systems through adaptive technology.